2005
DOI: 10.1021/ma050302r
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimers Clicked Together Divergently

Abstract: Dendrimers containing 1,4-triazole linkages between each generation were grown divergently via the Click chemistry inspired Huisgen 1,3-dipolar cycloaddition reaction in the presence of a Cu(I) catalyst. The monomeric unit (1-propargylbenzene-3,5-dimethanol) contained the alkyne functionality, while the core (1,2-bis(2-azidoethoxy)ethane) and growing dendrimers presented the azide groups necessary for this type of Click reaction. The first generation dendrimer was also functionalized with alkyne termini to dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
151
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(153 citation statements)
references
References 87 publications
0
151
0
2
Order By: Relevance
“…Subsequently, Wooley et al 30 reported on the divergent growth approach to Fre´chet-type dendrimers using Click chemistry, resulting in either azide or acetylene terminated dendrimers.…”
Section: Dendrimersmentioning
confidence: 99%
“…Subsequently, Wooley et al 30 reported on the divergent growth approach to Fre´chet-type dendrimers using Click chemistry, resulting in either azide or acetylene terminated dendrimers.…”
Section: Dendrimersmentioning
confidence: 99%
“…Since then, this Huisgen cycloaddition has been widely employed to synthesize or modify various dendrimers. [11,14,15,[55][56][57][58][59][60][61] Similarly, Diels-Alder reactions have found application in dendrimer synthesis and modification. McElhanon and Wheeler prepared dendrons and dendrimers that had thermoresponsive properties, owing to the reversibility of the Diels-Alder reaction.…”
Section: Role Of Click Chemistry In Multifunctional Polymer Designmentioning
confidence: 99%
“…The click chemistry reaction CuAAC is a very efficient, versatile, and popular reaction that has found several applications in many fields to achieve the preparation of very diverse molecules ranging from small compounds to polymers, hydrogel and other larges entities, including dendrimers (Wu et al, 2004;Joralemon et al, 2005;Malkoch et al, 2005;Fernández-Megia et al, 2006;Franc, Kakkar, 2010). Following a convergent strategy based on CuAAC reaction, the synthesis of a new class of glycodendrons with full control of the structure was developed.…”
Section: Glycodendritic Systems Based On the Cu (I) Catalyzed Azide-amentioning
confidence: 99%